2021
DOI: 10.3390/nano11030640
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TOPO and TOPO-CdSe/ZnS Quantum Dots on Luminescence Photodynamics of InP/InAsP/InPHeterostructure Nanowires

Abstract: The passivation influence by ligands coverage with trioctylphosphine oxide (TOPO) and TOPO including colloidal CdSe/ZnS quantum dots (QDs) on optical properties of the semiconductor heterostructure, namely an array of InP nanowires (NWs) with InAsP nanoinsertion grown by Au-assisted molecular beam epitaxy on Si (111) substrates, was investigated. A significant dependence of the photoluminescence (PL) dynamics of the InAsP insertions on the ligand type was shown, which was associated with the changes in the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
4
0
4
Order By: Relevance
“…Earlier in [6,7], we showed the possibility of growing practically 100% coherent InP/InAsP/InP NOCs concerning the silicon substrate. In [3,7] it was found that the application of the TOPO layer containing CdSe/ZnS colloidal dots (QD) to the array consisting of InP/InAsP/InP hybrid nanostructure NNCs. leads to a significant increase in the duration and intensity of InAsP nano wave (NV) luminescence.…”
Section: Introductionmentioning
confidence: 91%
“…Earlier in [6,7], we showed the possibility of growing practically 100% coherent InP/InAsP/InP NOCs concerning the silicon substrate. In [3,7] it was found that the application of the TOPO layer containing CdSe/ZnS colloidal dots (QD) to the array consisting of InP/InAsP/InP hybrid nanostructure NNCs. leads to a significant increase in the duration and intensity of InAsP nano wave (NV) luminescence.…”
Section: Introductionmentioning
confidence: 91%
“…Наличие коллоидной оболочки приводит как к росту общей длительности свечения QW и QI, так и особенному росту длительности и вклада второй компоненты свечения у QI. Такая подпитка излучающего состояния QI, возникающая при наличии коллоидной оболочки, может быть связана не только с обратным переносом возбуждения с близкорасположенных к QI ловушек, но и с новыми гибридными состояниями, образованными при взаимодействии лиганда с поверхностью наночастицы [23,26,28,29]. Такие состояния энергетически близки к излучающему состоянию и способны захватывать электроны или дырки.…”
Section: экспериментальные условияunclassified
“…В работе [29] обращено внимание на то, что увеличение длительности свечения и выхода люминесценции достигается при возбуждении в области прозрачности пассивирующего коллоида ТОРО-CdSe/ZnS QD (635 и 1064 nm). С этим эффектом связывается существенная роль эффекта обратного переноса.…”
Section: экспериментальные условияunclassified
See 2 more Smart Citations